A liver‐specific long noncoding RNA with a role in cell viability is elevated in human nonalcoholic steatohepatitis. Issue 3 (18th July 2017) - Atanasovska, Biljana; Rensen, Sander S.; van der Sijde, Marijke R.; Marsman, Glenn; Kumar, Vinod; Jonkers, Iris; Withoff, Sebo; Shiri‐Sverdlov, Ronit; Greve, Jan Willem M.; Faber, Klaas Nico; Moshage, Han; Wijmenga, Cisca; et al.
Abstract : Hepatocyte apoptosis in nonalcoholic steatohepatitis (NASH) can lead to fibrosis and cirrhosis, which permanently damage the liver. Understanding the regulation of hepatocyte apoptosis is therefore important to identify therapeutic targets that may prevent the progression of NASH to fibrosis. Recently, increasing evidence has shown that long noncoding (lnc) RNAs are involved in various biological processes and that their dysregulation underlies a number of complex human diseases. By performing gene expression profiling of 4, 383 lncRNAs in 82 liver samples from individuals with NASH (n = 48), simple steatosis but no NASH (n = 11), and healthy controls (n = 23), we discovered a liver‐specific lncRNA ( RP11‐484N16.1 ) on chromosome 18 that showed significantly elevated expression in the liver tissue of NASH patients. This lncRNA, which we named lnc18q22.2 based on its chromosomal location, correlated with NASH grade ( r = 0.51, P = 8.11 × 10 –7 ), lobular inflammation ( r = 0.49, P = 2.35 × 10 –6 ), and nonalcoholic fatty liver disease activity score ( r = 0.48, P = 4.69 × 10 –6 ). The association of lnc18q22.2 to liver steatosis and steatohepatitis was replicated in 44 independent liver biopsies ( r = 0.47, P = 0.0013). We provided a genetic structure of lnc18q22.2 showing an extended exon 2 in liver. Knockdown of lnc18q22.2 in four different hepatocyte cell lines resulted in severe phenotypes ranging from reduced cell growth to lethality. This observation was consistent with pathway analyses of genes coexpressed with lnc18q22.2 in human liver or affected by lnc18q22.2 knockdown. Conclusion : We identified an lncRNA that can play an important regulatory role in liver function and provide new insights into the regulation of hepatocyte viability in NASH. (Hepatology 2017;66:794–808).